Phytochemical Analysis of Different Parts of Acalypha Indica L. (Journal of Bio-Science, 2021)
Acalypha indica L. is an herbaceous medicinal plant, which is grown abundantly in Bangladesh. Bangladeshi people typically use various parts of this plant for various primary healthcare treatments. The current research was conducted to check and quantify various phytochemicals and mineral components of the assorted parts of Acalypha indica L. The screening analysis shows that studied all phytochemicals were present in the leaf part but not in stem and shoot parts and some were missing or trace amount in root. Total phenol, flavonoid, and tannins content on a dry weight basis ranged from 0.53-0.82 mg GAE/g, 0.02-1.47 mg QE/g and 0.21-0.32 mg TAE/g respectively. Among the phytochemicals the leaf contains the highest amount of flavonoid (1.47 mg QE/g), and lowest in stem (0.02 mg QE/g). Similarly, the amount of minerals like Fe, Zn, K and Pb was 0.23-0.40 mg/kg, 0.01- 0.021 mg/kg, 1.55-2.85 mg/kg and 0.149-0.204 mg/kg respectively. K was the largest volume of mineral for both leaf and stem. Lowest quantity of Zn was observed in most cases. This finding indicates that the studied plant might be good source of phytochemicals.J. Bio-Sci. 29(1): 69-77, 2021 (June)